HATE SPEECH MOTIVES OF NETIZEN ON INSTAGRAM SOCIAL MEDIA - B, Nur Fitriani; Mahmud, Murni; Burhamzah, Muftihaturrahmah (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
This article investigated and examined the motives behind hate speech on Instagram.  The subject is a well-known politician, Joe Biden the President of the United States. This article uses qualitative research techniques. The data were collected from screenshots in the politician comment columns. The transcriptions were interpreted and grouped using the theory of Pinker (2011) and the occurrences of motives were analyzed by the idea of King and Sutton (2013). The findings showed that: (1) Netizen generate motives of Instrumental Violence in response to fear. (2) Netizen generate motives of Power in response to a social entity. (3) Netizen generate motives of Revenge in response to retaliating or punishing someone. (4) Netizen generate motives of Ideology in response to psychological damage (5) Lastly, Netizen generate motives of Sadism in response to seeking pleasure by hurting another person physically or emotionally. Keywords: Hate Speech, Motives, Netizen.